2023
DOI: 10.1177/20552076231183552
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to unsupervised exercise in sedentary individuals: A randomised feasibility trial of two mobile health interventions

Abstract: Introduction Adherence to unsupervised exercise is poor, yet unsupervised exercise interventions are utilised in most healthcare settings. Thus, investigating novel ways to enhance adherence to unsupervised exercise is essential. This study aimed to examine the feasibility of two mobile health (mHealth) technology–supported exercise and physical activity (PA) interventions to increase adherence to unsupervised exercise. Methods Eighty-six participants were randomised to online resources ( n =  44, females n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…By incorporating the social science model and adapting to users’ heterogeneous characteristics and dynamic health behaviors, the reinforcement learning method offers a promising solution. 13 , 43 Experimental studies conducted by Forman et al 43 demonstrated the effectiveness of reinforcement learning in promoting increased exercise and achieving cost savings in digital health service. This research aims to improve exercise intervention effects in digital health service by addressing the limitations of existing approaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By incorporating the social science model and adapting to users’ heterogeneous characteristics and dynamic health behaviors, the reinforcement learning method offers a promising solution. 13 , 43 Experimental studies conducted by Forman et al 43 demonstrated the effectiveness of reinforcement learning in promoting increased exercise and achieving cost savings in digital health service. This research aims to improve exercise intervention effects in digital health service by addressing the limitations of existing approaches.…”
Section: Discussionmentioning
confidence: 99%
“… 12 The results of these studies correspond with previous several systematic reviews and empirical studies that have demonstrated the efficacy of digital health services in exercise guidance. 13 15 …”
Section: Introductionmentioning
confidence: 99%
“…Although PA is a crucial element for T2DM and GDM therapies there are some complications in its implementation, especially when the training is unsupervised. The unsupervised PA sessions may be ineffective, because of poor adherence and compliance to the training regimen, mainly due to lack of knowledge, personalization and support from exercise specialists [ 193 ]. However, the unsupervised PA is generally low cost and highly accessible what seems to be of great importance in certain circumstances i.e., COVID-19 pandemic.…”
Section: Feasibility and Usability Of Pa Treatmentsmentioning
confidence: 99%
“…Biometric data such as HR are recorded through a wrist worn fitness tracker to inform exercise counselling delivered by healthcare professionals. Recently, we have shown that the use of mHealth supported counselling leads to adherence of 113%±68 (participants exercised more often than prescribed) and is superior to self-directed web-based exercise in sedentary office workers at risk of CV disease 12…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have shown that the use of mHealth supported counselling leads to adherence of 113%±68 (participants exercised more often than prescribed) and is superior to self-directed web-based exercise in sedentary office workers at risk of CV disease. 12 …”
Section: Introductionmentioning
confidence: 99%